2002
DOI: 10.1017/s0956793302000225
|View full text |Cite
|
Sign up to set email alerts
|

Common Lands in Spain, 1800–1995: Persistence, Change and Adaptation

Abstract: The analyses and interpretations that the social sciences have been making in recent decades on the theme of common property call for a fresh look at the history of the commons. Such a vision no longer considers them as resources necessarily destined to disappear, but rather attempts to discover what forces have acted on their historical trajectory. From this perspective, this paper analyses the evolution of common lands in Spain over the nineteenth and twentieth centuries. To that end, it rests on an interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…A detailed study of the data shows that the "crimes" reported were related to traditional activities carried out in the woodlands like ploughing, livestock grazing and timber firewood gathering; therefore, it seems that, to a certain extent, their origin lies in state constraints and prohibitions. On the other hand, the Central Government's attempt to commodify common properties was not successful either; in northern regions of Spain, traditional uses persisted in woodlands (Balboa 1990;GEHR 1999;Jiménez Blanco 2002) and the commons systems were flexible enough to adapt to a changing economic context (Iriarte Goñi 2002). However, in terms of social history, critical approaches can be found about the way the State dispossessed peasants and local powers of competencies and favoured interests which had nothing to do with the rural communities (Moreno Fernández 1996;Balboa 1999).…”
Section: State Intervention In Common Land Management (Ii): Forest Enmentioning
confidence: 99%
“…A detailed study of the data shows that the "crimes" reported were related to traditional activities carried out in the woodlands like ploughing, livestock grazing and timber firewood gathering; therefore, it seems that, to a certain extent, their origin lies in state constraints and prohibitions. On the other hand, the Central Government's attempt to commodify common properties was not successful either; in northern regions of Spain, traditional uses persisted in woodlands (Balboa 1990;GEHR 1999;Jiménez Blanco 2002) and the commons systems were flexible enough to adapt to a changing economic context (Iriarte Goñi 2002). However, in terms of social history, critical approaches can be found about the way the State dispossessed peasants and local powers of competencies and favoured interests which had nothing to do with the rural communities (Moreno Fernández 1996;Balboa 1999).…”
Section: State Intervention In Common Land Management (Ii): Forest Enmentioning
confidence: 99%
“…35 There is evidence that the quality of education decreased during the second half of the 19th century as the number of teachers per pupil decreased (Núñez, 1992: 237). resources became a crucial source of complementary incomes in those areas that were more successful in resisting privatisation pressures (Iriarte, 2002;Jiménez Blanco, 2002). Therefore, by complementing households' incomes, commons distinctively contributed to sustaining the demand for education.…”
Section: Resultsmentioning
confidence: 99%
“…They highlight the capacity of Spanish society to adapt the general functions and the specific uses of the commons to changes in social and economic terms (GEHR 1994;Iriarte-Goñi 2002;Lana 2008). On the other hand, some works which study rural areas and commons in a historical perspective, emphasise the fact that enforcement of central laws on commons in Spain had been quite lax, allowing different regions with different economic and social features to apply the laws in different ways (Gallego et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The catalogs of public forests published in 1859, 1862, and 1901 served a dual purpose: privatization of those lands declared alienable (disentailment policy), and the conservation and protection of woodland for those remaining under state or village control. Historians agree that the quality of these statistics is poor, not least because of the short period that the engineers allowed for processing information, but this did not prevent completion of the privatisation policy (to an extent even greater than initially registered) or affect the bases of forest policy (Sanz-Fernández, 1985GEHR 1991GEHR , 1994GEHR , 1999GEHR , 2002López-Estudillo 1992;Iriarte-Goñi 2002;Pérez-Soba 2008). Significantly, strengthening the state by modernising the administrative apparatus, and maintenance of a harsh dictatorship in the middle decades of the 20th Century have not provided unambiguous statistical results in this area.…”
mentioning
confidence: 99%